1997
DOI: 10.1002/(sici)1096-9128(199706)9:6<621::aid-cpe310>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

SPMD programming in Java

Abstract: SUMMARYWe consider the suitability of the Java concurrent constructs for writing high-performance SPMD code for parallel machines. More specifically, we investigate implementing a financial application in Java on a distributed-memory parallel machine. Despite the fact that Java was not expressly targeted to such applications and architectures per se, we conclude that efficient implementations are feasible. Finally, we propose a library of Java methods to facilitate SPMD programming. ©1997 by John Wiley & Sons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
1998
1998

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A very interesting related theme is the implementation on the IBM POWERparallel System SP machine of a Java run-time system with parallel threads [18], using message passing to emulate shared memory. A very interesting related theme is the implementation on the IBM POWERparallel System SP machine of a Java run-time system with parallel threads [18], using message passing to emulate shared memory.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…A very interesting related theme is the implementation on the IBM POWERparallel System SP machine of a Java run-time system with parallel threads [18], using message passing to emulate shared memory. A very interesting related theme is the implementation on the IBM POWERparallel System SP machine of a Java run-time system with parallel threads [18], using message passing to emulate shared memory.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…The projects which focus on Java-based parallel computing include ATLAS [6], Charlotte [7], JPVM [8], JavaParty [9], Javelin [10], ParaWeb [11] and WebFlow [12]. Similarly, there have been proposals for Web-enabled virtual machines as a base for the High Performance Computing and Communication (HPCC) platform [13], to use Java in an SPMD programming model [14], and to extend Java with global pointers and remote service request mechanisms from the Nexus communication library [15]. Unfortunately, all but Charlotte and Javelin fail to take advantage of Web browsers in bringing distributed computing to every-day users.…”
Section: Metacomputing On the Webmentioning
confidence: 99%
“…JPVM provides a message passing interface to Java stand-alone applications, but not applets. Projects such as JavaParty and [14] require running a Java process to act as a runtime environment (in the case of JavaParty, this process is called the LocalJP). ParaWeb includes a distributed implementation of the Java Virtual Machine.…”
Section: Metacomputing On the Webmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrete event simulations are known to be computationally intensive, where the control of the computational process is responsible for a significant amount of the complexity and execution time. In different studies that evaluate the potential of Java as a high-performance computing language, it is indicated that certain improvements are necessary for successful usage [1,2]. On the other hand, Java offers an efficient and flexible simulation engine for DES with its complex control of the computational process.…”
Section: Introductionmentioning
confidence: 99%